RICE MILLING WASTE MANAGEMENT STRATEGY IN REALIZING A CIRCULAR ECONOMY BASED ON A GREEN ECONOMY - Elis Zunita Anzar Wati; Syuhada’ Syuhada’; Ahmad Munir Hamid (Nurul Jadid University, 2025)
AbstractThis study aims to analyze the strategy of rice milling waste management in order to realize a circular economy based on the green economy in Petiyin Tunggal Village. Rice milling waste such as husks, bran, and straw that have not been optimally utilized have great potential to be processed into value-added products. The circular economy and green economy approaches are the basis for creating a waste management system that is not only environmentally friendly, but also has a positive economic and social impact. This study uses a qualitative method with a case study approach, through field observations, in-depth interviews, and documentation. The results of the study indicate that there is a great opportunity for the development of community-based waste management innovations, such as the use of husks as alternative fuels and the processing of bran into animal feed. The recommended strategies include strengthening local institutions, waste management training, and collaboration with the private sector and government. Thus, rice milling waste management can not only reduce environmental impacts but also encourage green economic growth at the village level.